Motif dan Proses Pembuatan Kewatek pada Desa Bantala Kecamatan Lewolema Kabupaten Flores Timur - Uran, Brigita Elisabet KR.; Mudmainna, Mudmainna; Titu, Maria Anita; Masi, Reinaldis (SENTRI: Jurnal Riset Ilmiah, 2025)
Tenun Ikat is a traditional art form created by Lamaholot women as a medium to express the cultural identity and philosophy of life of the local community. This study aims to describe the motifs, meanings, and process of making Kwatek weaving in the Dona Tobo Ikat Weaving Group in Lewolema, as well as to understand the cultural meaning contained within it as an effort to strengthen local identity. The method used is a qualitative descriptive method through observation, interviews, and documentation. The results show that this group consists of 12 housewives who produce three main types of weaving: Kewatek for women, Nowing for men, and Selendang as a small woven cloth. The woven motifs are passed down from generation to generation and are believed to be sacred motifs revealed by the ruler of nature. Each motif depicts the values ​​of ancestral heroism and symbolizes the traditional three-burner wedding ceremony typical of the Lewolema area. The weaving process includes three main stages: preparation, dyeing, and weaving, which must be carried out carefully to produce beautiful and meaningful motifs. This study concludes that ikat weaving not only functions as a traditional craft, but also as a means of cultural preservation and identity transmission between generations.